Religion and Chinese society - Lagerwey, John (Chinese University Press : École française d'Extrême-Orient, 2004)
Thirty years ago, Hu Shih's views of Chinese society and history were representative of Sinology in general: China itself had no native religion, just local customs; its only real religion was an import, Buddhism. These views have now been completely overturned, with massive implications for our understanding not only of China but also of humanity as a whole: it is no longer possible to imagine that at least one major traditional society constructed and construed itself without reference to a non-mundane world that permeated every facet of society, and it therefore becomes indispensable for students of China to take the history of Chinese religion into account and for students of religion to take into account the Chinese experience of and Chinese categories for dealing with religious phenomena. The present volumes contain a selection of twenty-one essays presented in a conference convened jointly by the Ecole francaise d'Extreme-Orient and the Centre for the Study of Religion and Chinese Society of the Chinese University of Hong Kong, on "Religion and Chinese Society: The Transformation of a Field and Its Implications for the Study of Chinese Culture" held on May 29-June 2, 2000. The collection aims at providing as wide a coverage as possible of recent research in the history of Chinese religion and seeks to draw some tentative conclusions about the implications for the study of Chinese religion and society in general.